Discussion on trend of female solo traveller / Qurratu Aini Nazihah Nashrudin, Nur Anira Alfitri and Noor Hafizah Abdul Halim - Nashrudin, Qurratu Aini Nazihah; Alfitri, Nur Anira; Abdul Halim, Noor Hafizah (2017)
As for the purposes of this paper, firstly we would like to fills a gap in our understanding trend of female solo travellers. Secondly is to determine the most impact between which is positive impact or negative impact that would affect to female solo traveller during their journey. Finally, our purposes of this discussion through its attention to female solo travellers, helps bridge our understanding about the needs, concerns and motives of women as tourists by recommend the suggestion that can use by female solo traveller during their trips.